2007
DOI: 10.1097/01.tp.0000261113.30757.d1
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Therapy for Acute Humoral Rejection After Kidney Transplantation

Abstract: A pilot study was performed on eight consecutive renal-transplant (RT) patients presenting with acute humoral rejection (AHR) to assess the efficacy of monoclonal anti-B cell antibodies, such as rituximab (375 mg/m weekly) for 3 to 5 consecutive weeks, in addition to plasma exchange (PE), steroids, mycophenolate mofetil, and tacrolimus. AHR was associated with increased serum creatinine, the appearance of donor-specific alloantibodies (DSA), and the presence of C4d in a transplant biopsy. After a follow-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
151
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 19 publications
3
151
1
3
Order By: Relevance
“…Rituximab has been clinically applied in the treatment of B cells related diseases including multiple myeloma (11). Tyden et al (12) found the effectiveness of Rituximab in patients with renal transplant rejection due to mismatched ABO blood type.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab has been clinically applied in the treatment of B cells related diseases including multiple myeloma (11). Tyden et al (12) found the effectiveness of Rituximab in patients with renal transplant rejection due to mismatched ABO blood type.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to perform c4d staining due to unavailability of the technique in our institution. Treatment options include plasmapheresis, high-dose corticosteroid pulses, and IVIG with varying success rate (4,5). Some of these antibodymediated rejection episodes are refractory to conventional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Becker et al fi rst reported successful treatment of such a steroid-resistant rejection episode with rituximab (6). Since then a number of case series and reports have been published with regards to success of rituximab in this particular indication (4,6). Rituximab is a chimeric murine/human anti CD 20 antibody which directly inhibits B cell proliferation by antibody-dependent, cell-mediated, and complement-mediated cytotoxicity (7).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Anti-CD20 antibodies (rituximab) have been used as rescue therapy for CD20-mediated refractory acute rejection with successful outcomes. 7,[10][11][12][13][14][15] Herein, we report a case of refractory acute cellular rejection with clusters of CD20-positive lymphocyte graft infiltrates, resistant to steroid pulses, plasmapheresis, and switching of immunosuppressive drug regimen, which was successfully treated with anti-CD20 antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 However, rituximab has been successful in only 75% of recipients with positive DSAs and C4d-positive humoral rejection, raising the question of effective use of rituximab without CD20 phenotyping of the graft cellular infiltrate. 12 The presence of CD20-positive lymphocyte clusters in the allograft interstitium represents a severe subset of cellular rejection. 9 The infiltrating CD20-positive B cells may function as efficient antigen-presenting cells for indirect allorecognition, forming intrarenal ectopic lymphoid structures and leading to development of chronic allograft dysfunction.…”
mentioning
confidence: 99%